Hippocampal atrophy, asymmetry, and cognition in type 2 diabetes mellitus. Issue 1 (22nd December 2017) - Milne, Nicole T.; Bucks, Romola S.; Davis, Wendy A.; Davis, Timothy M. E.; Pierson, Ronald; Starkstein, Sergio E.; Bruce, David G.
Abstract: Introduction: Type 2 diabetes mellitus is associated with global and hippocampal atrophy and cognitive deficits, and some studies suggest that the right hippocampus may display greater vulnerability than the left. Methods: Hippocampal volumes, the hippocampal asymmetry index, and cognitive functioning were assessed in 120 nondemented adults with long duration type 2 diabetes. Results: The majority of the sample displayed left greater than right hippocampal asymmetry (which is the reverse of the expected direction seen with normal aging). After adjustment for age, sex, and IQ, right (but not left) hippocampal volumes were negatively associated with memory, executive function, and semantic fluency. These associations were stronger with the hippocampal asymmetry index and remained significant for memory and executive function after additional adjustment for global brain atrophy. Conclusions: We conclude that asymmetric hippocampal atrophy may occur in type 2 diabetes, with greater atrophy occurring in the right than the left hippocampus, and that this may contribute to cognitive impairment in this disorder. These cross‐sectional associations require further verification but may provide clues into the pathogenesis of cognitive disorders in type 2 diabetes. Abstract : In this cross‐sectional study in patients with type 2 diabetes, hippocampal atrophy was asymmetric with more rightward atrophy than expected. Right but not left hippocampal volumes were associated with impaired memory and executive function. Asymmetric hippocampal atrophy, with greater tissue loss on the right, may be a feature of type 2 diabetes.